Observer design based on linearization via input–output injection of time-delay systems. Issue 18 (2016) - García–Ramírez, E.; Califano, C.; Márquez–Martínez, L.A.; Moog, C.H.
Abstract: An observer design is derived for a nonlinear time-delay system from its equivalence to the observer canonical form up to nonlinear input-output injection. These results are obtained by using algebraic tools. It is shown that it is not necessary to guarantee equivalence through bicausal change of coordinates. A practical case study is worked out for an electromechanical system. Simulation results are included to show the feasibility of the presented observers.